CRISPR-Cas9: bridging the gap between aging mechanisms and therapeutic advances in neurodegenerative disorders - Shamsi, Anas; Alrouji, Mohammed; AlOmeir, Othman; Tasqeruddin, Syed; Dinislam, Khuzin; Zuberi, Azna (Frontiers in Cellular Neuroscience, 2025)
Neurodegenerative diseases such as Alzheimer’s, Parkinson’s, Huntington’s, ALS, and spinocerebellar ataxia are becoming more prevalent as populations age, posing major global health challenges. Despite decades of research, effective treatments that halt or reverse these conditions remain elusive. Aging is the most significant risk factor in the development of these diseases, intertwining with molecular processes like DNA damage, mitochondrial dysfunction, and protein aggregation. Recent advances in gene-editing technologies, particularly CRISPR-Cas9, are beginning to shift the therapeutic landscape. This revolutionary tool allows for precise correction of genetic mutations associated with neurodegeneration, offering the potential for disease modification rather than symptom management alone. In this review, we explore how CRISPR-Cas9 is being leveraged to target key genes implicated in various neurodegenerative conditions and how it may overcome barriers posed by aging biology. We also examine the delivery systems and safety challenges that must be addressed before clinical application. With continued progress, CRISPR-Cas9 could mark a turning point in our ability to treat or even prevent age-related neurological decline.